Gramine promotes functional recovery after spinal cord injury via ameliorating microglia activation. Issue 16 (19th July 2021) - Lu, Xiaolang; Lu, Fengfeng; Yu, Jiachen; Xue, Xinghe; Jiang, Hongyi; Jiang, Liting; Yang, Yang
Abstract: In recent years, a large number of studies have reported that neuroinflammation aggravates the occurrence of secondary injury after spinal cord injury. Gramine (GM), a natural indole alkaloid, possesses various pharmacological properties; however, the anti‐inflammation property remains unclear. In our study, Gramine was investigated in vitro and in vivo to explore the neuroprotection effects. In vitro experiment, our results suggest that Gramine treatment can inhibit release of pro‐inflammatory mediators. Moreover, Gramine prevented apoptosis of PC12 cells which was caused by activated HAPI microglia, and the inflammatory secretion ability of microglia was inhibited by Gramine through NF‐κB pathway. The in vivo experiment is that 80 mg/kg Gramine was injected orthotopically to rats after spinal cord injury (SCI). Behavioural and histological analyses demonstrated that Gramine treatment may alleviate microglia activation and then boost recovery of motor function after SCI. Overall, our research has demonstrated that Gramine exerts suppressed microglia activation and promotes motor functional recovery after SCI through NF‐κB pathway, which may put forward the prospect of clinical treatment of inflammation‐related central nervous diseases.